El perfil pedagógico competente : un análisis a la luz del formador de formadores en la Licenciatura en Educación Física y Deportes de la Universidad San Buenaventura, Medellín, 2010 (2010)
ABSTRACT: The present article is part of the macro project “the competent profile of the educational one, analyzing its reality in the experience of the curriculum: A analysis in the light of training of the training ones in the Degree in Physical education and Sports of the University of San Buenaventura, Medellín”, in 2010. The orientation question concentrated in including/understanding which is the competent profile of educational of specific subjects in the use of strategies of generic and specific education the learning for the future professional qualification of and the state demands of the evaluation of the education superior, analyzing its eality in the experience of the curriculum, with the implementation of directions and educative purposes from the pedagogical proposal of Franciscan Paideia, own of the catholic, Franciscan and deprived University, space of the present study; as general mission to recognize knowledge, practices and speeches of the educational ones of specific subjects revealing strategies and competitions like key factor of success, reaching conclusions advisers to come in the continuous formation of the teaching staff, in the possible routes and scopes of the evaluation of the performance, in reflections in front of the processes of bonaventuriana identity and in prospective of you rule for a curricular redesign by competitions.